Adenoid cystic carcinoma of the floor of the mouth – A rare presentation - Chandresh Jaiswara; Neeraj Kumar Dhiman; Akhilesh Kumar Singh; Naresh Kumar Sharma; Vishal Verma; Arun Pandey (Journal of Oral Biology and Craniofacial Research)
Adenoid cystic carcinoma (ACC) is an unusual salivary gland malignancy that remains poorly understood. It is a slow growing but aggressive neoplasm with a tendency for recurrence. It is characterized by the proliferation of ductal (luminal) and myoepithelial cells in cribriform, tubular, solid, and cystic forms. Standard treatment, including surgery with postoperative radiation therapy, has attained reasonable local control rates, but distant metastases do not allow any improvement in the survival rate. The understanding of the molecular mechanisms driving ACC is quite rudimentary. We present a case of a 55-year-old female diagnosed with ACC involving the floor of the mouth with an aim to present the carcinoma's behavior, immunohistocytochemistry, the staining pattern, its treatment, and prognosis.